Experimental and parametric numerical investigation of finned heat sinks with organic and metallic phase-change materials. (15th August 2023) - Koronio, Elad; Sharar, Darin J.; Spector, Mark S.; Gal, Oren; Shockner, Tomer; Regev, Oren; Ziskind, Gennady
Highlights: PCM-based heat sink with plate fins and spreader for transient thermal management. Different heat sink materials and two PCM types with similar melting temperatures. Heat spreading, temperature evolution and detailed melting patterns in the sink. Advantageous performance of Field's metal vs. organic paraffin in heat accumulation. Dimensional analysis generalizing power inputs and material properties. Abstract: The use of phase change materials (PCMs) has gained much attention for applications of transient thermal management of electronic systems due to their high latent heat and ability to absorb heat near-isothermally. Because of their low thermal conductivity, PCMs are usually integrated with heat sinks to be used more efficiently. In this study a PCM-based heat sink with a generic structure of plate fins was investigated experimentally and numerically. The intentionally simple fin topology allowed focusing on the effects of various material properties rather than the commonly investigated geometry effects. Hence, two types of heat sink material, copper and aluminum, were examined, and two PCMs with similar melting temperatures but distinctly different thermal properties – a metallic alloy (Field's metal) and an organic paraffin (n-Octacosane), were used. Experimental findings allowed for validation of the numerical approach, used for a comprehensive parametric numerical study. The latter facilitated a more detailed investigation of the transient heat transfer processes, such as melting patterns and heat accumulation analyses, where the superior thermal properties of the metallic PCM manifested in more efficient latent heat accumulation, resulting in reduced system peak temperatures. It was found that systems with Field's metal were able to accommodate up to 80% of the energy in the form of latent heat, which is 10 percentage points higher than achieved using the organic paraffin. A dimensional analysis accounting for power inputs and material properties was conducted, and a generalized behavior was achieved for a normalized time in terms of Fourier and Stefan numbers, and thermal diffusivities ratio.